Conocimientos y actitudes de las enfermeras del servicio de emergencia en la prevención de infecciones intrahospitalarias Hospital Belén de Trujillo - Vásquez Montoya, Karina Magaly (2019)
The present cross-sectional descriptive type research was carried out in order to determine the relationship between the level of knowledge of nurses towards the prevention of in-hospital infections and the attitude on biosafety standards emergency service Hospital Belén de Trujillo 2019, the sample universe consisted of 35 nurses who met the inclusion criteria established to whom two instruments were applied, one on the level of knowledge and the second on the attitude of nurses on biosafety standards, for the analysis The Pearson correlation coefficient statistical test in compliance with bivariate normality was used Coming to the following conclusions: 2.9% (1 participants) of the nurses surveyed presented a medium level of knowledge about the Prevention of Inpatient Infections, while 97.1% (34 participants) were found at the high level, 8.6% (3 participants) of the nurses surveyed, presented an intermediate attitude, while 91.4% (32 participants) of the total nurses surveyed presented a favorable attitude. There is a significant relationship between the level of knowledge about the prevention of hospital infections and the attitude of nurses to biosecurity standards, the value of Pearson's correlation coefficient 0.05 (p = 0.032 <0.05).